Phase change amino acid salt separates into CO2-rich and CO2-lean phases upon interacting with CO2. (1st January 2016) - Wang, Xianfeng; Akhmedov, Novruz G.; Hopkinson, David; Hoffman, James; Duan, Yuhua; Egbebi, Adefemi; Resnik, Kevin; Li, Bingyun
Graphical abstract: Highlights: Innovative phase change amino acid salt solvent is developed for CO2 capture. Amino acid salt solution is turned into a CO2 -rich phase and a CO2 -lean phase upon simple bubbling with CO2 . The developed solvent captures the most CO2 (∼90%) in the CO2 -rich phase. NMR spectroscopy was used to identify the species in the solution. Abstract: Concerns over global climate change have led to strong research emphasis worldwide on reducing the emission of greenhouse gases like CO2 . One avenue for carbon emission reduction is using CO2 capture and storage from industrial sources. Having low toxicity and low vapor pressure and being resistant to oxidation, natural amino acids could be a better choice over current carbon capture materials. In this study, we pioneered a unique phase change amino acid salt solvent concept in which amino acid salt solution was turned into a CO2 -rich phase and a CO2 -lean phase upon simple bubbling with CO2 and most importantly, this solution captured the most CO2 (∼90%) in the CO2 -rich phase. Bicarbonate was found to be dominant in the CO2 -rich phase, which had a high CO2 loading capacity and good regenerability and cycling properties. Such a phase change amino acid salt solvent may provide unique solutions for industries to reduce CO2 and other harmful emissions.